The Importance of the QSAR-QSPR Methodology to the Theoretical Study of Pesticides - Duchowicz, Pablo Román (2013)
In this paper, we reviewed various interesting applications of the Quantitative Structure-Activity/Property Relationships (QSAR-QSPR) Theory in pesticide research, with special emphasis on studies developed during the last decade. Different types of chemical structures were considered as pesticide agents. The environmental fate of pesticides is determined by partitioning between environmental compartments, and by transport and degradation processes. It is known that ecotoxicity assessment is essential before placing new chemical substances on the market, and so we reviewed the QSAR-QSPR applications on different properties, such as the Bioconcentration Factor, Soil/Sediment Sorption Coefficient, Toxicity, Aqueous Solubility, and Air to Water Partitioning. Finally, we revised different specific studies in this field